1994
DOI: 10.1213/00000539-199410000-00009
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Reversal of Heparin Effect with Heparinas

Abstract: This study was designed to evaluate the potential in vitro use of heparinase to eliminate functionally active heparin prior to performing whole blood (WB) prothrombin time (PT) and activated partial thromboplastin time (APTT) assays. A total of 250 U/kg of heparin for cardiopulmonary bypass (CPB) was administered to 30 cardiac surgical patients in three consecutive, divided doses (20, 80, and 150 U/kg) at 15-min intervals. Blood specimens were obtained prior to heparin administration (baseline) and 10 min afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, some animal studies revealed its renal toxicity [41]. Some studies indicate that heparinase is highly effective in eliminating the anticoagulant activity of heparin in vitro in plasma from cardiac surgical patients [42]. On the other hand, heparinase used for heparin anticoagulation reversal in patient after aorto-coronary bypass graft surgery has inferior safety profile, compared to protamine [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, some animal studies revealed its renal toxicity [41]. Some studies indicate that heparinase is highly effective in eliminating the anticoagulant activity of heparin in vitro in plasma from cardiac surgical patients [42]. On the other hand, heparinase used for heparin anticoagulation reversal in patient after aorto-coronary bypass graft surgery has inferior safety profile, compared to protamine [43].…”
Section: Discussionmentioning
confidence: 99%
“…Its heparin-neutralizing abilities rely on the cleavage of alpha-glycosidic linkages at the ATIII binding site and prevent a heparin-AT-thrombin complexation [92,93]. Lots of studies confirmed the reversal of the heparin effect by heparinase at aPTT, PT and TT tests [14,94]. Heparinase restores the thrombin activity, decreases coagulation time and has a minimal effect on platelets [93,95].…”
Section: Commercially Available Agents For Heparins Removal In Diagno...mentioning
confidence: 99%
“…References with asterisk describe the effect of samples from DOAC or heparin treated patients. PT dabigatran [60,81] TT dabigatran [81] dabigatran [60] dRVVT, aPTT-LA dabigatran [60,81] APC-R dabigatran [60,81] FVII, FVIII, FIX and FX assays dabigatran [60,81] Added in concentration of 125 µg/ml [87] to plasma samples from DOAC-treated patients* TGA dabigatran [82]* Andexanet alfa Added in concentration of 100 µg/ml [92], 200 µg/ ml [93,94] to plasma spiked with DOAC ACT betrixaban [87] edoxaban [87] aPTT rivaroxaban [87], edoxaban [87], betrixaban [87] apixaban [87] PT rivaroxaban [87], apixaban [87], edoxaban [87], betrixaban [87] PiCT rivaroxaban [87], apixaban [87], edoxaban [87], betrixaban [87] Anti-FXa assay rivaroxaban [87], apixaban [87], edoxaban [87], betrixaban [87] dRVVT, aPTT-LA rivaroxaban [88] FVIII, FIX assays rivaroxaban [89] CAT rivaroxaban [87], apixaban [87], edoxaban [87], betrixaban [87] Protamine sulfate Added in concentration of 0-200 µg/ml [109,117,118] to normal plasma spiked with heparin...…”
Section: Removal Of Anticoagulants Completementioning
confidence: 99%